2018
DOI: 10.1097/ncc.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients' Long-term Experiences of Participating in a Comprehensive Lifestyle Intervention Study While Receiving Chemotherapy

Abstract: Background Lifestyle interventions seem promising with regard to cancer patients' potential for physical and psychological health benefits and as an empowerment tool. Nevertheless, there is a lack of knowledge concerning cancer patients' longer-term experiences of participating in comprehensive lifestyle interventions. Objective The aim of this study was to explore cancer patients' long-term experiences of participating in a 12-month individualized comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A possible reason for this difference may be due to the women’s physical level at the time of diagnosis. Other studies found that many cancer patients become more sedentary and inactive during treatment 40 . A systematic review by Lin et al 41 stated that a small number of randomized controlled trials and feasibility studies have documented that physical activity is feasible and safe for women with gynecological cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for this difference may be due to the women’s physical level at the time of diagnosis. Other studies found that many cancer patients become more sedentary and inactive during treatment 40 . A systematic review by Lin et al 41 stated that a small number of randomized controlled trials and feasibility studies have documented that physical activity is feasible and safe for women with gynecological cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found that many cancer patients become more sedentary and inactive during treatment. 40 A systematic review by Lin et al 41 stated that a small number of randomized controlled trials and feasibility studies have documented that physical activity is feasible and safe for women with gynecological cancer. In addition, a recent randomized counseling intervention study found that two-thirds of cervical cancer survivors did not meet national recommendations for health behaviors.…”
Section: Discussion and Critical Interpretationmentioning
confidence: 99%
“…For example, we learned that person-centered motivational interviewing and medically tailored meals are key ingredients for promulgating an adjustment to diagnosis and active coping with self-care. Furthermore, understanding how this food is medicine intervention worked is signi cant because a cancer diagnosis has complex psychological and physical impacts [22][23][24]. Patients report feeling overwhelmed by the complexity of care, feeling ill-prepared to manage side effects of treatment, isolated, unsupported, and "out of their depth" [23].…”
Section: Discussionmentioning
confidence: 99%
“…Patients report feeling overwhelmed by the complexity of care, feeling ill-prepared to manage side effects of treatment, isolated, unsupported, and "out of their depth" [23]. Despite this, cancer patients engaged in NutriCare and other nutrition and lifestyle interventions report creating personal growth since lifestyle changes are challenges that patients can control at a time of uncertainty [22,24]. This ability to learn and change despite experiencing adversity is remarkable but aligns with transformative learning and social-cognitive transition models where one is challenged to question existing habits for personal growth [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Patients report feeling overwhelmed by the complexity of care, feeling ill-prepared to manage side effects of treatment, isolated, unsupported, and “out of their depth” [ 34 ]. Despite this, cancer patients engaged in NutriCare and other nutrition and lifestyle interventions report creating personal growth since lifestyle changes are challenges that patients can control during a time of uncertainty [ 33 , 35 ]. This ability to learn and change despite experiencing adversity is remarkable but aligns with transformative learning and social-cognitive transition models where one is challenged to question existing habits for personal growth [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%